POLA KECEMASAN PASIEN YANG AKAN DILAKUKAN ANESTESI PADA OPERASI ELEKTIF DI INSTALASI BEDAH SENTRAL RSUD BHAKTI DHARMA HUSADA SURABAYA: POLA KECEMASAN PASIEN YANG AKAN DILAKUKAN ANESTESI PADA OPERASI ELEKTIF DI INSTALASI BEDAH SENTRAL RSUD BHAKTI DHARMA HUSADA SURABAYA - Muhammad Fauzi; Reko Priyonggo; Mokhtar Jamil (Jurnal Kesehatan Hesti Wira Sakti, 2023)
ABSTRACT Introduction: Preoperative anxiety is a normal response to life-threatening situations and conditions for patients. Preoperative anxiety is often associated with fear of surgical procedures, anesthetic procedures, and information needs fulfillment factors. Assessment of the right pattern of anxiety can determine the appropriate management in dealing with anxiety. The purpose of this study was to determine the anxiety patterns of preoperative patients at Bhakti Dharma Husada Hospital, Surabaya. Methods: This study used a quantitative descriptive method with a cross sectional approach. The research subjects included preoperative patients at Bhakti Dharma Husada Hospital, Surabaya. The sample is 68 people. Measurement of anxiety using the APAIS scale (Amsterdam preoperative anxiety and information scale). Data analysis using Descriptive Statistical Test. Results: The majority of respondents were female (58.8%), aged 26 -35 years (44.1%), had high school education (63.2%), had a general anesthesia plan (63.2%), and had no surgical experience ( 73.5 %). The majority of respondents experienced moderate anxiety (47.1%), then severe anxiety (32.4%), mild anxiety (14.7%), panic (5.9%), and not anxious (0%). The majority of respondents have an element of anxiety related to the need for information. Discussion: The pattern of respondents' anxiety based on the APAIS instrument shows that the majority of respondents in this study experienced moderate anxiety, with elements of anxiety related to the need for information. Researchers suggest that health workers always carry out an anxiety assessment before surgery, so that they can provide appropriate management in reducing patient anxiety. Keywords: Anxiety, Pre operative, Pre Anesthesia